The impact of Ethiopia's pilot community based health insurance scheme on healthcare utilization and cost of care. (January 2019) - Mebratie, Anagaw D.; Sparrow, Robert; Yilma, Zelalem; Abebaw, Degnet; Alemu, Getnet; Bedi, Arjun S.
Abstract: In June 2011, the Government of Ethiopia introduced a pilot Community Based Health Insurance (CBHI) scheme in rural parts of the country. Based on a fixed effects analysis of household panel data, this paper assesses the impact of the scheme on utilization of modern healthcare and the cost of accessing healthcare. It adds to the relatively small body of work that provides a rigorous evaluation of CBHI schemes. We find that in the case of public health facilities, enrolment leads to a 30–41% increase in utilization of outpatient care, a 45–64% increase in the frequency of visits and at least a 56% decline in the cost per visit. The impact on utilization and costs combined with a high uptake rate of almost 50% within two years of scheme establishment underlines the relative success of the Ethiopian scheme. While there are several reasons for this success, a comparative analysis of the design and execution of the Ethiopia CBHI with the existing body of work yields two distinct features. First, the Ethiopian scheme is embedded within existing government administrative structures and to signal government commitment, scheme performance and uptake is used as a yardstick to measure the success of the administration. Second, an existing social protection scheme was used to spread information, raise scheme awareness and encourage uptake of health insurance. The alignment of the interests of administrators with scheme performance and interlinking of social protection schemes are innovative design features that are worth considering as developing countries strive to enhance access to health care through voluntary insurance schemes. Highlights: Ethiopia's pilot community based health insurance scheme enhances health care use. The scheme also enhances financial protection. Scheme enrolees experience a 30 to 41 percent increase in health care utilization. Scheme enrolees experience, at least, a 56 percent decline in cost per visit. Scheme uptake and effects are promising from a universal health coverage perspective.